2022
DOI: 10.21203/rs.3.rs-1173826/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Clinical Features and Estimated Incidence of MIS-C in Cape Town, South Africa

Abstract: Background Multisystem inflammatory syndrome is a severe manifestation of SARS-CoV-2 in children. The incidence of MIS-C after infection is poorly understood. There are very few cohorts describing MIS-C in Africa despite MIS-C being more common in Black children worldwide. Methods A cohort of children with MIS-C and healthy children was recruited from May 2020 until May 2021 from the two main paediatric hospitals in Cape Town, South Africa. Clinical and demographic data were collected, and serum was tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 13 publications
1
24
1
Order By: Relevance
“…The median age was 3•98 years (range 1•71 − 7•44) and 70% of the children were male. Our colleagues in South Africa had a cohort of 68 patients with a much higher median age of 7 years (range 3•6-9•9) (15). The majority of our patients were African, re ecting the demographics of our nation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The median age was 3•98 years (range 1•71 − 7•44) and 70% of the children were male. Our colleagues in South Africa had a cohort of 68 patients with a much higher median age of 7 years (range 3•6-9•9) (15). The majority of our patients were African, re ecting the demographics of our nation.…”
Section: Discussionmentioning
confidence: 85%
“…In There are few reports of MIS-C is sub-Saharan Africa, which may lead to a presumption that this syndrome is not identi ed in these populations yet low and middle-income countries (LMICs) have the challenge of delayed vaccination, poor vaccine coverage, inadequate diagnostics, sub-optimal management options despite a relatively larger proportion of younger people in their population (15).…”
Section: Discussionmentioning
confidence: 99%
“…42 Therefore, on the global level, pediatric complications due to SARS-CoV-2 infection are most likely underreported and will continue to occur given the considerably lower vaccine coverage in LMICs. 42 In high income countries, such as the USA, the risk for MIS-C is increased in Black and Hispanic children. 30,41 This disparity could be due to socio-economic and health care access inequities, but genetic and environmental risk factors are still being explored.…”
Section: S E Vere D Is E a S E From Covid Doe S Not O Ccur Frequently...mentioning
confidence: 99%
“…Importantly, exact data on global SARS‐CoV‐2 infections in LMICs are often not available, especially when estimating pediatric cases. In fact, only recently a first study on MIS‐C was reported from South Africa 42 . Therefore, on the global level, pediatric complications due to SARS‐CoV‐2 infection are most likely underreported and will continue to occur given the considerably lower vaccine coverage in LMICs 42 .…”
Section: Severe Disease From Covid Does Not Occur Frequently In Child...mentioning
confidence: 99%
See 1 more Smart Citation